Factors associated with the resource allocation decisions of tertiary school administrators of Western and Central Visayas Regions VI and VII - Biboso, Tomasa N. 1930-
This study investigated the infuence of environmental, organizational and personal factors on the allocative decisions for research, capital outlay, extension and instruction of 42 tertiary school administrators from 12 state and 12 private colleges and universities and 9 technical schools. Stepwise multiple regression analysis and logarithmic transformation show that these factors are associated with resource allocation.